1998
DOI: 10.1001/archinte.158.6.641
|View full text |Cite
|
Sign up to set email alerts
|

Complication-Free Duration and the Risk of Development of Retinopathy in Elderly Diabetic Patients

Abstract: Background: Determining which diabetic patients are at risk for complications and targeting these patients for intensive therapy may avoid the unwanted consequences of hypoglycemia in low-risk patients. Since aging is associated with a decrease in the incidence of diabetic retinopathy, we assessed whether long complicationfree duration can define elderly patients at lower risk for future development of diabetic retinopathy. Methods: In a 10-year clinic-based study, we studied 833 type 2 diabetic patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
3
18
0
Order By: Relevance
“…The Blue Mountains study, which reported similar findings, also found that hyperglycemia was associated with moderate to severe retinopathy [22] . Cohen et al [23] found that the most important predictor of retinopathy in the older age group was the known duration of diabetes. The UK Prospective Diabetes Study reported that the age at diagnosis was not significantly associated with baseline prevalence of retinopathy, which was close to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The Blue Mountains study, which reported similar findings, also found that hyperglycemia was associated with moderate to severe retinopathy [22] . Cohen et al [23] found that the most important predictor of retinopathy in the older age group was the known duration of diabetes. The UK Prospective Diabetes Study reported that the age at diagnosis was not significantly associated with baseline prevalence of retinopathy, which was close to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia (16 -19) and longer duration of diabetes (3,16,18,19) are probably the most commonly reported associations with incidence of retinopathy. The presence of macroalbuminuria has been reported as a risk factor for the incidence of retinopathy (16,18), although not in all studies (20). We did not find a statistically significant association between hypertension and incidence or progression of retinopathy.…”
Section: Risk Factors Associated With Progression Of Retinopathymentioning
confidence: 99%
“…The authors concluded that diabetes duration was a significant, independent variable for development of retinopathy 262 . A study of 926 patients with type 1 and type 2 diabetes recruited from 7 hospital clinics in different geographic regions of Malaysia reported a similar finding.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…A prospective Israeli cohort study of 833 patients with T2DM from a diabetic outpatient clinic reported that patients who developed retinopathy were younger at their mean onset of diabetes (age 48.7 years) and had longer mean diabetes duration (13.2 years) than patients who did not develop retinopathy (mean age 53.4 years; mean duration 6.1) 262 . The authors concluded that diabetes duration was a significant, independent variable for development of retinopathy 262 .…”
Section: Type 2 Diabetesmentioning
confidence: 99%